Thinking the Anthropocene - Coy, Martin; Hafner, Robert (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
This editorial gives a short introduction to the different strands of the Anthropocene and ties together the contributions of this Special Issue.